A frequency selective surface loaded two-layer composite for tunable microwave absorption. (1st June 2022) - Zhao, Yiming; Wang, Qichao; Sun, Yungang; Xuan, Shanyong; Li, Minghang
Abstract: To obtain tunable microwave absorption, a strategy of constructing a frequency selective surface (FSS) on a two-layer composite is proposed. The designed FSS loaded two-layer composite is composed of a FSS constructed by evenly spaced circular copper sheet, an impedance matching layer (SiO2 fiber reinforced epoxy resin (EP) composite, SiO2f /EP) and a lossy layer. Both simulation and experiments indicate that the SiO2f /EP layer serves as a good impedance matching layer with increased microwave absorption efficiency. By analyzing the distributions of electric field, magnetic field as well as the power loss, the strong resonance should be attributed to the enhanced incident microwave caused by FSS.